2015
DOI: 10.1136/bmjqs-2015-ihiabstracts.2
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communication During Cardiac Intensive Care Unit Multidisciplinary Rounds Through Visual Display of Patient Daily Goals

Abstract: BackgroundThe care of critically ill children in intensive care units (ICU) has become increasingly complex. Utilization of multidisciplinary care teams leads to reduction in mortality and length of stay, prevention of adverse events, and improvement in quality of care. However, as the number of care providers grows and patient demand increases, coordination of multidisciplinary care becomes more complicated.ObjectivesTo improve communication during cardiac ICU multidisciplinary rounds.MethodsQuality improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These data suggest that visual data may be useful in explaining to patients why they are not eligible at the time of consultation for surgery. In fact, published data across medical disciplines reveal improved comprehension, 10–17 adherence, 18 and satisfaction 17,18 with the addition of visual information to patient–physician communications. This tool should be considered for what could be one of the most important conversations in a patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that visual data may be useful in explaining to patients why they are not eligible at the time of consultation for surgery. In fact, published data across medical disciplines reveal improved comprehension, 10–17 adherence, 18 and satisfaction 17,18 with the addition of visual information to patient–physician communications. This tool should be considered for what could be one of the most important conversations in a patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,13 Investigations focused on interventions to improve goal elicitation and patient satisfaction regarding whiteboard usage and nurse-led initiatives provided the inspiration for this project. 18,19,20 Recording daily goals on a whiteboard facilitates a consistent plan of care, goal directed care, and provides health care providers with a daily list of patient goals to review. 19 One quality improvement study focused on whether an educational intervention for nurses improved identification of patient daily goals.…”
Section: Review Of Literaturementioning
confidence: 99%
“…18,19,20 Recording daily goals on a whiteboard facilitates a consistent plan of care, goal directed care, and provides health care providers with a daily list of patient goals to review. 19 One quality improvement study focused on whether an educational intervention for nurses improved identification of patient daily goals. Overall, this study showed that the nurse educational intervention increased whiteboard documentation, articulation of goals, nurse collaboration concerning goals and patients felt more informed by nurses.…”
Section: Review Of Literaturementioning
confidence: 99%